PROPORTION OF ISOMORPHIC ERYTROCYTE URINE IN DIABETIC KIDNEY DISEASE WITH FLOW CYTOMETRY METHODS - Erica Catarina; Coriejati Rita; Basti Andriyoko; Ida Parwati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Hematuria can be found in diabetic kidney disease. Urinary erythrocytes morphology can differentiate hematuria in diabetic kidney disease from other glomerular disorders. Different etiologies need different management. Urinalysis with flowcytometry method can directly give information about urine erythrocyte morphology which is not obtained by the conventional method. The aim of this study was to determine the proportion of urinary isomorphic erythrocytes in diabetic kidney disease. This was a descriptive cross-sectional study in the Dr. Hasan Sadikin Hospital Bandung from July 2016 to July 2017. Subjects were 38 patients who have been diagnosed as diabetic kidney disease by clinicians and had hematuria. Random urine samples were collected for erythrocytes morphology assay by using flowcytometry method and u-ACR values by using spectrophotometry method. The result of this study was 57.9% male, with the most frequent age were 55-64 years old group (34.2%) and 63.2% from all subject were included in the macroalbuminuria category. In erythrocyte morphology assay, 84.2% was isomorphic erythrocyte which 83.3% was macroalbuminuria group. The proportion of hematuria in diabetic kidney disease with automated integrated urine flowcytometry method was dominated by isomorphic erythrocyte morphology. Isomorphic erythrocytes in DM did not mean absence of glomerular abnormalities.